2020
DOI: 10.1002/uog.20381
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement in MRI assessment of severity of placenta accreta spectrum disorders

Abstract: Objective To evaluate the level of agreement in the prenatal magnetic resonance imaging (MRI) assessment of the presence and severity of placenta accreta spectrum (PAS) disorders between examiners with expertise in the diagnosis and management of these conditions. Methods This was a secondary analysis of a prospective study including women with placenta previa or low‐lying placenta and at least one prior Cesarean delivery or uterine surgery, who underwent MRI assessment at a regional referral center for PAS di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…We have reported previously that both ultrasound and MRI have a high diagnostic accuracy for detecting PAS, with reported values of sensitivity and specificity of more than 90% in the overall population of women at risk for PAS [8][9][10][11] . In the present review, posterior PAS was missed on ultrasound in about half of the cases, while the detection rate by MRI was higher, with more than two-thirds of cases detected prenatally.…”
Section: Comparison With Other Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported previously that both ultrasound and MRI have a high diagnostic accuracy for detecting PAS, with reported values of sensitivity and specificity of more than 90% in the overall population of women at risk for PAS [8][9][10][11] . In the present review, posterior PAS was missed on ultrasound in about half of the cases, while the detection rate by MRI was higher, with more than two-thirds of cases detected prenatally.…”
Section: Comparison With Other Systematic Reviewsmentioning
confidence: 99%
“…Both ultrasound and MRI have been shown to have an overall high diagnostic performance in detecting PAS [8][9][10] . However, these results are applicable mainly to women with anterior placenta previa, and it has yet to be determined whether the performance of prenatal imaging in detecting these anomalies is retained when placental invasion occurs in the posterior wall of the uterus 8,9,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of the US and MRI findings had fair or moderate interobserver agreement. Past studies have also shown suboptimal agreement for findings of PAS [24,25,28,42,43]. The limited interreader agreement reflects the often ambiguous nature of the assessment of imaging features for PAS, which requires experience and can be difficult in complex cases.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The clinical diagnosis of placenta previa often relies on clinical manifestations and ultrasound imaging. Although ultrasound is good for the diagnosis of placenta previa in pregnant women, it is easily affected by objective conditions such as overfilling of the bladder and fetal position [ 14 ]. In recent years, MRI has performed extremely well in obstetrics.…”
Section: Discussionmentioning
confidence: 99%